THE INFLUENCE OF LAND USE AND INFRASTRUCTURE ON ECONOMIC GROWTH IN EAST NUSA TENGGARA PROVINCE - Anjelo Gabriel Abur; Fransina w. Ballo; Olivia l. Eunike Tomasowa (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the effect of land use and infrastructure on economic growth in the Province of East Nusa Tenggara. Land use and infrastructure are important factors in regional development because they support economic activities, increase productivity, and facilitate the distribution of goods and services. However, the archipelagic geographical characteristics of East Nusa Tenggara and the existing limitations in infrastructure are presumed to affect the effectiveness of these factors in promoting economic growth. This research employed a quantitative approach with a descriptive-associative method. The study utilized secondary data covering the period 2015–2024 obtained from the Central Bureau of Statistics (BPS) of East Nusa Tenggara Province and was supported by primary data collected through interviews with relevant institutions. Data were analyzed using multiple linear regression to examine the influence of land use and infrastructure on economic growth. The results indicate that land use has a regression coefficient of 0.231 with a significance value of 0.617 (> 0.05), meaning that it does not have a significant effect on economic growth. Infrastructure has a regression coefficient of -0.150 with a significance value of 0.144 (> 0.05), indicating that it also does not significantly affect economic growth. Simultaneously, land use and infrastructure do not have a significant effect on economic growth, as shown by the F-test significance value of 0.194 (> 0.05). The coefficient of determination (R²) is 0.441, which means that 44.1% of the variation in economic growth can be explained by land use and infrastructure variables, while the remaining 55.9% is influenced by other factors outside the research model. The study concludes that land use and infrastructure have not yet significantly contributed to economic growth in East Nusa Tenggara Province. This condition is attributed to the suboptimal utilization of land resources, low intensity of productive land use, limitations in infrastructure quality, and the lack of integration between land utilization, infrastructure development, and productive economic sectors. Therefore, development policies should not only focus on physical infrastructure development but also emphasize improving human resources, technology, investment, and the effectiveness of infrastructure utilization to achieve sustainable economic growth. Keywords: Land Use, Infrastructure, Economic Growth, Multiple Linear Regression, East Nusa Tenggara Province.